EFEKTIVITAS PROMOSI DALAM MENINGKATKAN PENJUALAN PRODUK KPR SUBSIDI DiTENGAH PERSAINGAN PASAR : ANALISIS STRATEGI PEMASARAN DALAM ISLAM (Studi pada BTN KCPS Jombang) - Putri, Nurdiana; Haryanti, Peni (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
This study aims to analyze the effectiveness of promotional strategies in increasing sales of subsidized Home Ownership Credit (KPR) products amidst increasingly competitive market and implementation of marketing strategies in Islam. The method used in this study is a qualitative method with a case study approach at one of the banks that offers subsidized KPR products through interviews and direct observation with Customer Financing Officers at BTN KCPS Jombang. The results of the study indicate that promotions carried out through personal selling are effective in attracting potential customers, especially in the low-income segment. However, tight market competition demands continuous innovation in promotional strategies so that subsidized KPR products can remain competitive as well as marketing strategies based on Islam.